Diagnosis of X-linked Alport syndrome (Experimental biology, 2015)
In the study, the gene COL4A5 was genotyped by direct sequencing of the family with X-linked Alport syndrome.Based on the results of genotyping of both members of the family identified previously described mutationekzone2204G 25> A, due to the replacement of glycine with glutamic acid in position 735. They are the carriers of theheterozygous mutation allele B25 exon (Gly735Glu). As a result, it can be concluded the mutation Gly735Glu, ispathogenic and associated with juvenile type of hereditary nephritis, which is characterized by early development ofchronic renal failure (16 years).
Keywords: hematuria; X-linked Alport syndrome; glomerular basement membrane; type IV collagen; COL4A5